I try to calculate the two options for possible. But I think it has something wrongs that cant find out the answer. Please see the following details.

For the Q1a answer, md^2 x/dt^2 = -kx/m, wo^2 = k/m

For the Q1b1

(Option 1)

By acceleration, dx^2/dt^2 = -w1^2(x)

By acceleration, dFapp^2/dt^2 = - w1^2(Fapp)

Therefore, md^2 x/dt^2 = -w1^2(x) + w1^2(Fapp)

For the Q1a answer, md^2 x/dt^2 = wo^2(x) = k/m

md^2 x/dt^2 = -w1^2(x) - w1^2(Fapp) = - wo^2(x)

w1^2(Fapp) = wo^2(x) -w1^2(x)

w1^2(Fapp) /[wo^2 -w1^2] = (x)

(Option 2)

md^2 x/dt^2 = -kw1^2(x) + w1^2(Fapp)

= wo^2(x) (m) [xmax cos w1 t] + F1 cos w1t

I don't know how to do...

For the Q1b2

Like as something wrong for Q1b1, so i couldn't show that!

Please advise me where is wrong! Thanks a lot!

For the Q1a answer, md^2 x/dt^2 = -kx/m, wo^2 = k/m

For the Q1b1

(Option 1)

By acceleration, dx^2/dt^2 = -w1^2(x)

By acceleration, dFapp^2/dt^2 = - w1^2(Fapp)

Therefore, md^2 x/dt^2 = -w1^2(x) + w1^2(Fapp)

For the Q1a answer, md^2 x/dt^2 = wo^2(x) = k/m

md^2 x/dt^2 = -w1^2(x) - w1^2(Fapp) = - wo^2(x)

w1^2(Fapp) = wo^2(x) -w1^2(x)

w1^2(Fapp) /[wo^2 -w1^2] = (x)

(Option 2)

md^2 x/dt^2 = -kw1^2(x) + w1^2(Fapp)

= wo^2(x) (m) [xmax cos w1 t] + F1 cos w1t

I don't know how to do...

For the Q1b2

Like as something wrong for Q1b1, so i couldn't show that!

Please advise me where is wrong! Thanks a lot!

### Recently Asked Questions

- Please refer to the attachment to answer this question. This question was created from Case Study_Description.docx.

- Please refer to the attachment to answer this question. This question was created from Case Study_Description.docx.

- Please refer to the attachment to answer this question. This question was created from Case Study_Description.docx.